Pax6 Lengthens G1 Phase and Decreases Oscillating Cdk6 Levels in Murine Embryonic Cortical Progenitors - Mi, Da; Manuel, Martine; Huang, Yu-Ting; Mason, John O.; Price, David J. (Frontiers in Cellular Neuroscience, 2018)
Pax6 is a key regulator of the rates of progenitor cell division in cerebral corticogenesis. Previous work has suggested that this action is mediated at least in part by regulation of the cell cycle gene Cdk6, which acts largely on the transition from G1 to S phase. We began the present study by investigating whether, in addition to Cdk6, other Pax6-regulated cell cycle genes are likely to be primary mediators of Pax6’s actions on cortical progenitor cell cycles. Following acute cortex-specific deletion of Pax6, Cdk6 showed changes in expression a day earlier than any other Pax6-regulated cell cycle gene suggesting that it is the primary mediator of Pax6’s actions. We then used flow cytometry to show that progenitors lacking Pax6 have a shortened G1 phase and that their Cdk6 levels are increased in all phases. We found that Cdk6 levels oscillate during the cell cycle, increasing from G1 to M phase. We propose a model in which loss of Pax6 shortens G1 phase by raising overall Cdk6 levels, thereby shortening the time taken for Cdk6 levels to cross a threshold triggering transition to S phase.